2020
DOI: 10.1002/chem.202002267
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic In Situ and Ex Situ Studies of Phase Transformations in Molecular Co‐Crystals

Abstract: Co-crystallisation is widely explored as ar oute to improve the physical properties of pharmaceuticala ctive ingredients, but little is known about the fundamental mechanisms of the process. Herein, we apply ah yphenated differential scanning calorimetry-X-ray diffraction technique to mimic the commercialh ot melt extrusion process, and explore the heat-induceds ynthesis of as eries of new co-crystals containingi sonicotinamide. These comprise a1 :1 cocrystal with 4-hydroxybenzoica cid, 2:1a nd 1:2s ystemsw it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The melting of the cocrystal at lower temperatures compared to the pure components (PZQ and SUB) can be explained by the fact that the crystal lattice and the Gibbs energy of the cocrystal are lower than those of the individual components. The decrease in the melting point and enthalpy of fusion in the cocrystal compared to praziquantel alone indicates a decrease in the thermodynamic stability and implicitly a higher solubility . From the comparison of the TG curve of the cocrystal PZQ·SUB (Figure b) with the TG curves of the initial ingredients, it was observed that the decomposition of the cocrystal occurs more slowly compared to the initial ingredients, and the mass loss is lower.…”
Section: Resultsmentioning
confidence: 98%
“…The melting of the cocrystal at lower temperatures compared to the pure components (PZQ and SUB) can be explained by the fact that the crystal lattice and the Gibbs energy of the cocrystal are lower than those of the individual components. The decrease in the melting point and enthalpy of fusion in the cocrystal compared to praziquantel alone indicates a decrease in the thermodynamic stability and implicitly a higher solubility . From the comparison of the TG curve of the cocrystal PZQ·SUB (Figure b) with the TG curves of the initial ingredients, it was observed that the decomposition of the cocrystal occurs more slowly compared to the initial ingredients, and the mass loss is lower.…”
Section: Resultsmentioning
confidence: 98%
“…The obtained solids were stored in a fridge (6 °C) before characterisation by DSC-XRD. DSC measurements were performed with a modified Q20 DSC (TA Instruments), with the instrument modification, experiment set up and data analysis protocols being the same as described previously ( Clout et al, 2020 ; Pang et al, 2022 ). The DSC was mounted and aligned on the sample stage in the experimental hutch of Beamline I12 (JEEP) ( Drakopoulos et al, 2015 ) at the Diamond Light Source to allow a monochromated X-ray beam (0.5 mm × 0.5 mm; λ = 0.234 Å) to pass through holes in the DSC cell.…”
Section: Methodsmentioning
confidence: 99%
“…As with spray drying and spray freeze drying which can create high solute supersaturation, a growing body of research suggests the feasibility of preparing kinetically stable cocrystals through electrospraying, [115][116][117][118][119][120][121] jet dispensing, thermal inkjet printing, etc. [122][123][124][125][126] The success of these production technologies was witnessed by the significant increase of literature reports in the past decade. For instance, Dyba et al showcased the equivalence of using electrospraying to facilitate the exclusive formation of the metronidazole-gallic acid form II cocrystal, comparable to the spray drying method.…”
Section: Emerging Approaches For Elusive Cocrystal Productionmentioning
confidence: 99%